Measurement and Uniform Formulation of Soil-Water Characteristic Curve for Compacted Loess Soil with Different Dry Densities. (17th March 2021) - Wang, Yu; Li, Tonglu; Li, Ping; Lei, Yulu; Lawrence, David D.
Abstract : To investigate the effect of dry density on the soil-water characteristics of compacted soil, loess used as filling in the land-making project of the Yan'an new district was collected and compacted to five initial dry densities of 1.40, 1.50, 1.60, 1.70, and 1.80 g/cm 3, respectively. The soil-water characteristic curves (SWCCs) of all specimens in the range of 0–10 5  kPa were measured using the filter paper method. The measured data were fitted using the Fredlund and Xing equation for each initial dry density. The SWCCs have obvious differences in a suction range below 100 kPa and overlap when the suction range is higher. This suggests that the SWCC of compacted soil is independent of the initial dry density in the high suction range, but the correlation with the initial dry density exists in the low suction range. Therefore, the correlation functions of the parameters in the Fredlund and Xing equation with respect to the initial dry density were regressed, respectively. By substituting these functions into the Fredlund and Xing equation, the state surface function of θ w − ψ − ρ d was obtained and can reflect the SWCCs of all densities of the filled soil to support the further investigation of the unsaturated behavior of compacted soil.